Development and validation of upper secondary students’ attitudes towards digital competence instrument in Malaysia - Ghafar, Nur Faeeza Abd.; Razali, Fazilah; Ayub, Ahmad Fauzi Mohd (Intelektual Pustaka Media Utama, 2026)
Digital competency is increasingly vital for students in today’s technology-driven world. Despite efforts to enhance digital skills in education, measuring students’ attitudes toward digital competency remains a challenge, especially in developing contexts like Malaysia. This paper develops and validates the upper secondary students’ attitudes towards digital competency instrument (USSADCI) in Malaysia, providing a psychometrically reliable and valid tool specifically designed while addressing a gap in previous research. Using the Rasch measurement model (RMM), the USSADCI measures constructs such as digital technology application, problem-solving, interpersonal skills, data and information literacy, content creation, digital security, and digital citizenship. A survey method was employed, collecting 47 feedback from students in the urban secondary schools and 43 feedback from the rural secondary schools in the State of Perak. The analysis found that the reliability of the item was 0.96 with a separating index of 4.77. While the respondent’s reliability was 0.92 with a separating index of 3.42. The 14 items were removed due to misfit, resulting in a final 42-item instrument. The study concludes that USSADCI is a robust tool for measuring digital competence attitudes in secondary education. Future research should expand its use to other regions and demographics, exploring the longitudinal impact of digital competence attitudes on students’ academic performance and digital readiness.